Legal Protection of Children’s Privacy Rights from Global EdTech Governance Oversight - Putu Fairnanda Sastra Devi; Dewa Gede Sudika Mangku; Ni Putu Rai Yuliartini (proceedings.icesy, 2026)
The massive shift to education technology (EdTech) has exposed a critical vulnerability in international law: the systematic exploitation of children’s data. A 2022 Human Rights Watch report revealed that 89% of analyses EdTech products engage in data practices that risk or violate children’s rights, yet international law enforcement remains weak. This research examines the legal gap between the principle of "The Best Interests of the Child" and the commercial reality of cross-border data mining. Using normative legal methods with a statutory approach, the study analyses the inadequacy of current international instruments, such as the UN Convention on the Rights of the Child, in addressing modern digital surveillance. The findings suggest a "governance vacuum" where global platforms transcend national jurisdictions, leaving children in developing countries inadequately protected. This article urges the need for a binding international framework that mandates rigorous algorithmic accountability and cross-border enforcement mechanisms. By aligning global policies and laws, the international community can foster a resilient and inclusive digital education ecosystem that prioritizes human rights over commercial interests.